Engineered nanomaterials enhance drug delivery strategies for the treatment of osteosarcoma - Zhang, Haorui; Luo, Ping; Huang, Xiaojun (Frontiers in Pharmacology, 2023)
Osteosarcoma (OS) is the most common malignant bone tumor in adolescents, and the clinical treatment of OS mainly includes surgery, radiotherapy, and chemotherapy. However, the side effects of chemotherapy drugs are an issue that clinicians cannot ignore. Nanomedicine and drug delivery technologies play an important role in modern medicine. The development of nanomedicine has ushered in a new turning point in tumor treatment. With the emergence and development of nanoparticles, nanoparticle energy surfaces can be designed with different targeting effects. Not only that, nanoparticles have unique advantages in drug delivery. Nanoparticle delivery drugs can not only reduce the toxic side effects of chemotherapy drugs, but due to the enhanced permeability retention (EPR) properties of tumor cells, nanoparticles can survive longer in the tumor microenvironment and continuously release carriers to tumor cells. Preclinical studies have confirmed that nanoparticles can effectively delay tumor growth and improve the survival rate of OS patients. In this manuscript, we present the role of nanoparticles with different functions in the treatment of OS and look forward to the future treatment of improved nanoparticles in OS.